New Synthesis of Gold- and Silver-Based Nano-Tetracycline Composites - Djafari, Jamila (2017)
J.D., C.L,. and J.F.-L. conceived and designed the experiments; J.D. and J.F.-L. performed the synthesis and characterization of the TC functionalized Ag and Au NPs, as well as the metal-ion sensing studies. C.M., T.S., G.I., and P.P. studied the bacterial interactions with the NPs. C.T. provided the TC bacterial resistant strains. All authors have analyzed the data. J.F.L., J.D., C.L, J.L.-C., C.M., P.P., and G.I. wrote and corrected the paper. C.L., J.L.-C., G.I., and P.P. contributed with reagents/materials/analysis tools. J.F.-L. thanks Fundacao para a Ciencia e a Tecnologia-Ministerio de Ciencia e Educacao (FCT/MEC) (Portugal) for his postdoctoral grant reference SFRH/BPD/93982/2013. J.D. thanks Proteomass Scientific Society for a PhD research grant. This work was supported by the Associate Laboratory for Green Chemistry LAQV, which is financed by national funds from FCT/MEC (UID/QUI/50006/2013) and co-financed by the European Regional Development Fund (ERDF) under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265) and by the Unidade de Ciencias Biomoleculares Aplicadas-UCIBIO, which is financed by national funds from FCT/MEC (UID/Multi/04378/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728). All authors thank the Proteomass Scientific Society, General Funds (Portugal) for financial support.